The Determinant of Trust in Telemedicine: A Systematic Review - Dhika Purnastyasih; Eko Prasojo (Magister Administrasi Publik, 2023)
Telemedicine is a form of utilizing technology in the health sector that has been rapidly adopted globally, especially since the COVID-19 pandemic. Telemedicine has the potential to be a solution to overcoming the problem of access to health services. Despite its great benefits, telemedicine also encountered obstacles in its implementation, and among them that are fundamental is trust. Trust in telemedicine is unique and different from electronic services because it involves personal and sensitive data. This study examine the role of trust in telemedicine and the factors that determine trust in telemedicine services through a systematic review. This study uses a systematic review method of related publications from 2012 to 2022 derived from the Scopus database. A selection process was carried out based on the eligibility criteria set for 1196 related publications, so 17 articles were obtained, which were analyzed in this study. Based on a literature review, trust in telemedicine is multi-dimensional and is shaped by various factors of trust that influence each other. The main factors are trust in the care organization, trust in the care professional, trust in the treatment, and trust in the technology. Another factor that determines trust in telemedicine is individual’s characteristics, such as age, gender, level of education, technological literacy, income, type of disease, health condition, frequency of use, and experience. Moreover, there are factors external from the individual characteristics that can also determine trust in telemedicine, such as family support, living area, community, and social media, the COVID-19 pandemic, and the existence of policies and regulations that support and enforced.